2020
DOI: 10.3390/plants9111526
|View full text |Cite
|
Sign up to set email alerts
|

Type of Explant Affects In Vitro Development and Multiplication Success of the Rare Halophyte Plant Honckenya Peploides L. Ehrh

Abstract: The sea sandwort—Honckenya peploides (L.) Ehrh. is—a rare halophilous plant growing on dunes and is an endangered species on the Polish coast. It contributes to the stabilization of volatile sandy substrate, facilitating the colonization of other species. The present study determined the reaction of two types of explant: apical shoot fragments and fragments from a lower portion of the shoot. Apical shoot fragments were used to propagate and root sea sandwort plants due to the positive impact on the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…In a study where spray with sea water was performed separately on female and male individuals, it was shown that it had a positive effect on root and shoot growth only on the background of nutrient addition-stimulated growth [187]. Using stem apical and nodal explants for propagation in tissue culture, it was evident that root growth was inhibited already at 25 mM NaCl in cultivation medium, but shoot growth was negatively affected only at 75 mM NaCl [188].…”
Section: Honckenya Peploidesmentioning
confidence: 99%
“…In a study where spray with sea water was performed separately on female and male individuals, it was shown that it had a positive effect on root and shoot growth only on the background of nutrient addition-stimulated growth [187]. Using stem apical and nodal explants for propagation in tissue culture, it was evident that root growth was inhibited already at 25 mM NaCl in cultivation medium, but shoot growth was negatively affected only at 75 mM NaCl [188].…”
Section: Honckenya Peploidesmentioning
confidence: 99%
“…The MS basal medium, at full, half-, or less frequently double-concentrated, is the most used for rooting, as found for S. brachiata , which suggests that shoot multiplication conditions, as well as genotype, may also influence the rooting efficiency [ 61 , 62 , 134 ]. For instance, Kulpa et al [ 81 ] described how the origin of the shoot (apical > basal) and the type of cytokinin used for shoot multiplication of H. peploides had a significant impact on the size and number of roots—meta-Topolin (mT) improved spontaneous rooting when compared to BAP and Kin [ 81 ]. Similarly, the shoots of J. roemerianus regenerated with BAP supplementation induced the production of adventitious roots, but not those supplemented with TDZ [ 87 ].…”
Section: Micropropagation Of Halophyte Plantsmentioning
confidence: 99%